UNDERSTANDING FINANCIAL LITERACY TOWARDS RETIREMENT - Annisa, Firda Nur; Prajawati, Maretha Ika; S, Basir (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2022)
Retirement for some people is a fear in itself because many people are not ready to face it. Good and comfortable financial condition before retirement is a syndrome that some people are not ready to retire. Therefore, it is important before entering retirement to understand financial literacy as early as possible to prepare for retirement. The purpose of this study is to dig deeper into the understanding of several state civil servants in the pre-retirement period related to financial literacy in facing retirement. This study uses a qualitative method. Research objects that meet the criteria as informants are 13 people. The research data was carried out by means of observation, interviews and documentation. The research was conducted in Mekarsari Village, Sragen. Retirement is not the end of everything. The results showed that the informants understood financial literacy to prepare for retirement in 3 ways. The first way is frugal living, the second is a budgeting pattern and profit seeker. Financially independent retirement can be achieved if in the preretirement period you manage to set aside your income, have savings and also invest for life supplies in retirement.